Secure scalable streaming enabling transcoding without decryption - Wee, S.J.; Apostolopoulos, J.G. (2001 International Conference on Image Processing, 2001)
We present a method of secure scalable streaming (SSS) that enables low-complexity and high-quality transcoding to be performed at intermediate, possibly untrusted, network nodes without compromising the end-to-end security of the system. SSS encodes video into secure scalable packets using jointly designed scalable coding and progressive encryption techniques. This combination allows downstream transcoders to perform transcoding operations such as bitrate reduction and spatial downsampling by simply truncating or discarding packets, and without decrypting the data. Secure scalable packets have unencrypted headers that can provide hints such as optimal truncation points to downstream transcoders. Using these hints, downstream transcoders can perform RD-optimal transcoding for fine-grain bitrate reduction. The SSS transcoding operation has low complexity and is stateless, so SSS transcoders can support many simultaneous transcoding sessions. SSS works with existing scalable image and video compression standards and systems including Motion JPEG-2000, 3D subband coding, and MPEG-4 FGS.